Potential role of HTLV-1 Tax-specific cytotoxic t lymphocytes expressing a unique t-cell receptor to promote inflammation of the central nervous system in myelopathy associated with HTLV-1 - Tanaka, Yukie; Sato, Tomoo; Yagishita, Naoko; Yamauchi, Junji; Araya, Natsumi; Aratani, Satoko; Takahashi, Katsunori; Kunitomo, Yasuo; Nagasaka, Misako; Kanda, Yoshinobu; Uchimaru, Kaoru; Morio, Tomohiro; et al. (Frontiers in Immunology, 2022)
Human T-lymphotropic virus 1 (HTLV-1) infection causes two serious diseases: adult T-cell leukemia/lymphoma (ATL) and HTLV-1-associated myelopathy (HAM). Immunological studies have revealed that HTLV-1 Tax-specific CD8+ cytotoxic T-cells (Tax-CTLs) in asymptomatic carriers (ACs) and ATL patients play an important role in the elimination of HTLV-1-infected host cells, whereas Tax-CTLs in HAM patients trigger an excessive immune response against HTLV-1-infected host cells infiltrating the central nervous system (CNS), leading to local inflammation. Our previous evaluation of HTLV-1 Tax301-309 (SFHSLHLLF)-specific Tax-CTLs (Tax301-309-CTLs) revealed that a unique T-cell receptor (TCR) containing amino acid (AA)-sequence motif PDR, was shared among HLA-A*24:02+ ACs and ATL patients and behaved as an eliminator by strong activity against HTLV-1. However, it remains unclear whether PDR+Tax301-309-CTLs also exist in HLA-A*24:02+ HAM patients and are involved in the pathogenesis of HAM. In the present study, by high-throughput TCR repertoire analysis technology, we revealed TCR repertoires of Tax301-309-CTLs in peripheral blood (PB) of HLA-A*24:02+ HAM patients were skewed, and a unique TCR-motif PDR was conserved in HAM patients (10 of 11 cases). The remaining case dominantly expressed (-DR, P-R, and PD-), which differed by one AA from PDR. Overall, TCRs with unique AA-sequence motifs PDR, or (-DR, P-R, and PD-) accounted for a total of 0.3-98.1% of Tax301-309-CTLs repertoires of HLA-A*24:02+ HAM patients. Moreover, TCR repertoire analysis of T-cells in the cerebrospinal fluid (CSF) from four HAM patients demonstrated the possibility that PDR+Tax301-309-CTLs and (-DR, P-R, and PD-)+Tax301-309-CTLs efficiently migrated and accumulated in the CSF of HAM patients fostering increased inflammation, although we observed no clear significant correlation between the frequencies of them in PB and the levels of CSF neopterin, a known disease activity biomarker of HAM. Furthermore, to better understand the potential function of PDR+Tax301-309-CTLs, we performed immune profiling by single-cell RNA-sequencing of Tax301-309-CTLs, and the result showed that PDR+Tax301-309-CTLs up-regulated the gene expression of natural killer cell marker KLRB1 (CD161), which may be associated with T-cell activation and highly cytotoxic potential of memory T-cells. These findings indicated that unique and shared PDR+Tax301-309-CTLs have a potential role in promoting local inflammation within the CNS of HAM patients.